Microstructure variability and macroscopic composite properties of high performance fiber reinforced cementitious composites - Li, Victor C.; Wang, Shuxin (Probabilistic engineering mechanics, 2006)
High performance fiber reinforced cementitious composites have made major advances in recent years, to the point where they are being adopted in building and bridge constructions. The most significant advantage of HPFRCC over conventional concrete is their high tensile ductility. However, the tensile strain capacity has been observed to vary, most likely as a result of the variability of the microstructure derived from the processing of these materials. This paper describes the composite property variability, as well as the variability of the material microstructure. Scale linkage is discussed. In particular, the tensile stress–strain curves, and the crack pattern on uniaxially loaded specimens are presented. The treatment of random fibers in micromechanical models, and tailoring of matrix flaw size distribution for saturated multiple cracking are examined. It is suggested that robust composite properties can be achieved by deliberate control of microstructure variability. Some open issues concerning the randomness of microstructures and possibly related macroscopic behavior are also identified. Further gains in composite property control may be expected from improvements in characterization and modeling of the microstructure randomness.